2020
DOI: 10.1021/acs.jafc.0c03621
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Steroids in Bovine Serum: Validation of a Reliable LC-MS/MS Method and In Vivo Studies with Boldenone Undecylenate and Testosterone Propionate

Abstract: Serum analysis has received much attention in regulatory analysis of food-producing animals, especially for anabolic steroids. The possibility of confirming the parent drugs with minimum metabolization enables the detection of intact steroid esters, whose identification represents unequivocal proof of drug administration. This work involved the development and validation of a quantitative LC-MS/MS method to determine 30 steroids and steroid esters in bovine serum. Sensitivity was improved using microwave-assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…It could be observed that B1 and B4 exhibited larger detection windows for αBO, up to D78. As for serum, βBO was detected through D92 for both animals . The obtained concentration values for βBO in serum are presented in Figure S1 (Supporting Information).…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…It could be observed that B1 and B4 exhibited larger detection windows for αBO, up to D78. As for serum, βBO was detected through D92 for both animals . The obtained concentration values for βBO in serum are presented in Figure S1 (Supporting Information).…”
Section: Resultsmentioning
confidence: 91%
“…Ultrapure water was generated by Gehaka, Master Sigma 100 (Gehaka, São Paulo, Brazil). The other chemicals related to serum analysis have been described elsewhere …”
Section: Materials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations